Retrospective analysis of pembrolizumab-related adverse reactions and death outcomes based on the FAERS database - Huilin Xu; Ying Huang; Nan Zhao; Han Hu; Dedong Cao (BMC Cancer)
Abstract Objective This study aimed to analyze the characteristics of adverse reactions in cancer patients treated with Pembrolizumab based on the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database, and to assess the characteristics and risk factors of fatality reports. Methods The study data was sourced from the FAERS database, collecting adverse event reports related to Pembrolizumab from 2013 to June 2024. The main analysis variables included gender, age, cancer type, country, reporter type, and adverse reaction outcomes. Descriptive statistics, univariate analysis, and multivariate Logistic regression models were used to assess the relationship between each variable and fatal outcome. Results A total of 46,883 adverse reactions were collected, including 5,483 reports with fatal outcomes. The number of events has been increasing since 2013, especially peaking in 2022 and 2023. The United States and Japan had the highest number of adverse reaction reports. The number of serious events reported increased significantly with age, especially in the 51–65 and 66–80 age groups. The age of patients who died was concentrated in the elderly group (≥ 65 years old), and the median treatment duration time of pembrolizumab was 17 days. Analysis showed that gender (OR = 0.75; 95%CI: 0.71–0.80, p < 0.01), age (OR = 0.89; 95%CI: 0.84–0.96, p < 0.01), and ingredients count (OR = 1.92; 95%CI: 1.84–2.01, p < 0.01) were significantly associated with the treatment duration of pembrolizumab. Conclusion The serious adverse reactions in cancer patients treated with Pembrolizumab are closely related to patient individual characteristics and cancer types. It is necessary to strengthen the monitoring of high-risk groups such as the elderly in clinical treatment to reduce the risk of fatal outcomes.